TrAgLor, an implementation of IEEE LOM draft standard in agriculture and life sciences. (2nd June 2009) - Cebeci, Zeynel; Erdogan, Yoldas; Kara, Murat
The Turkish Agricultural Learning Objects Repository (TrAgLor) is a multilingual IEEE LOM Draft Standard compatible Learning Objects (LO) repository. It has been developed as a test-bed to enable the storage, search and retrieval of objects or their metadata related with agriculture, food, veterinary and environmental sciences for learners and educators in Turkey. The main purpose for developing TrAgLor was to implement a demonstrative repository system that focuses on various technical aspects related to storage, retrieval and exchange of LO produced for Turkish higher Institutions. Accordingly, this paper primarily aims to introduce and discuss the architecture and functions of the repository on LO and metadata management, searching and interoperability in addition to some preliminary findings on usage and contribution levels to the repository.